P2-S8.09 What are they asking? An analysis of STD related calls to CDC-INFO. (10th July 2011) - Kachur, R; Thompson, N; Haecker, S; Jones, R
Abstract : Background: Launched in 2005, CDC-INFO is the Center for Disease Control and Prevention's (CDC) national contact center, which responds to health related enquiries from the general public and healthcare providers and partners 24 h a day, 7 days a week. STD-related topics have consistently been among the top ten most frequently asked questions. In order to better understand what information is being sought, telephone calls and emails to CDC-INFO were analysed for STD specific topics and topic frequencies. Methods: STD-related calls and emails made to CDC-INFO between October 2009 and September 2010 (FY2010) were analysed for topic content and frequency. Results: In FY2010, there were 44339 STD-related calls and 2123 STD-related emails to CDC-INFO. Enquiries fell into 11 main categories. The top 3 telephone enquiries were about Herpes (26%), Testing and Counselling (25%) and Human Papillomavirus (HPV) (18%). The top 3 email enquiries were about Herpes (34%), HPV (21%) and Other Sexually Transmitted Diseases (12%). The most common STD question to CDC-INFO was Can you help me locate a STD testing site in my area?", although the largest percentage of questions were about Herpes, followed by HPV, Testing and Counselling and Chlamydia. Findings from CDC-INFO correlate with findings from traffic to the Division of STD Prevention (DSTDP) website (http://www.cdc.gov/std/ ) which also finds that Genital Herpes and HPV are the most frequently visited pages on the website. A CDC-INFO satisfaction survey conducted between October 2009—and March 2010 found that among STD related telephone callers, 63% were female, over 65% were 34 years old or younger, 34% were White and 35% were Black/African American. Of those qualitatively interviewed, 91% (n=199) reported learning new information as a result of the call to CDC-INO and 68% indicated a desire to change a behaviour based on the new information. Reducing risky sexual behaviour was the most common type of behaviour change indicated. Conclusions: Information about Genital Herpes, HPV, and STD testing locations are the most frequently sought after topics by those accessing CDC-INFO. Regularly analysing enquiries to CDC-INFO can help the DSTDP identify topics of most concern to the general public, possibly detect emerging trends and tailor communications accordingly. Further research should be done to determine how DSTDP communication and prevention priorities correspond to general public enquiries and concerns.